2014
DOI: 10.1021/ef500923b
|View full text |Cite
|
Sign up to set email alerts
|

2-(Methylamino)ethanol for CO2 Absorption in a Bubble Reactor

Abstract: This paper deals with the study of carbon dioxide capture using 2-(methylamino)ethanol (MAE) aqueous solutions. The reaction was studied in a bubble column reactor (BCR), and the most important aspects of the process, such as the hydrodynamic behavior (bubble size distribution, gas holdup, and interfacial area) and absorption phenomena (load of carbon dioxide and mass-transfer coefficient on the liquid phase), were discussed. The interfacial area was determined using a photographic method. Furthermore, the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…2-(Methylamino)­ethanol (MAE), a secondary amine, has already been proven to be a potential absorbent for CO 2 capture by some researchers. , MAE combines the characteristics of primary and tertiary amines of a high reaction rate with CO 2 and high CO 2 capture capacity, respectively. , Mimura et al studied the reaction kinetics between CO 2 and sterically hindered secondary alkanolamines, such as MAE, ethylaminoethanol (EAE), and butylamino ethanolamine (BAE), the results showed that MAE presents a higher reaction rate with CO 2 than the primary alkanolamine monoethanolamine (MEA) and the secondary alkanolamines EAE and BAE. Folgueira et al have studied the hydrodynamic behavior and the mass-transfer performance of CO 2 with aqueous MAE solution in a bubble column reactor (BCR), as well as the reaction mechanism using analysis by NMR technology. The results showed that the carbamate and bicarbonate are the main products at low and high CO 2 loadings, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…2-(Methylamino)­ethanol (MAE), a secondary amine, has already been proven to be a potential absorbent for CO 2 capture by some researchers. , MAE combines the characteristics of primary and tertiary amines of a high reaction rate with CO 2 and high CO 2 capture capacity, respectively. , Mimura et al studied the reaction kinetics between CO 2 and sterically hindered secondary alkanolamines, such as MAE, ethylaminoethanol (EAE), and butylamino ethanolamine (BAE), the results showed that MAE presents a higher reaction rate with CO 2 than the primary alkanolamine monoethanolamine (MEA) and the secondary alkanolamines EAE and BAE. Folgueira et al have studied the hydrodynamic behavior and the mass-transfer performance of CO 2 with aqueous MAE solution in a bubble column reactor (BCR), as well as the reaction mechanism using analysis by NMR technology. The results showed that the carbamate and bicarbonate are the main products at low and high CO 2 loadings, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, the ratio of the initial height of liquid in the column and the liquid height after injecting gas is measured. The gas holdup with this method is indicated by the following equation: …”
Section: Theorymentioning
confidence: 99%
“…MAE has a higher reaction rate than primary amines, but it shows higher absorption capacity than tertiary amines. Some researchers studied MAE and reported it as a potential solvent for CO 2 absorption in terms of CO 2 loading, heat effect, and reaction kinetics. AEEA is an unhindered diamine that has one primary amine and one secondary amine group. AEEA can absorb 2 mol of CO 2 and shows high CO 2 cyclic capacity, high values of second-order reaction rate, and lower regeneration energy.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this paper is to measure the viscosity and refractive index data of pure MAE, pure AEEA, aqueous MAE, aqueous AEEA with different concentrations (5,10,15,20,25, and 30 wt %), and aqueous blend of MAE and AEEA (25 + 5, 20 + 10, 15 + 15, 10 + 20, and 05 + 25 wt % MAE and AEEA) in the temperature range of 293.15−333.15 K. MAE and AEEA weight ratio was selected based on the literature data. Intervals of 5 wt % were selected randomly to measure experimental data and develop empirical correlation.…”
Section: Introductionmentioning
confidence: 99%